2017
DOI: 10.1111/are.13559
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis reveals olfactory-related genes expression in large yellow croaker (Larimichthys crocea) regulated by taurine: May be a good phagostimulant for all-plant protein diets

Abstract: Taurine is usually included in fish feed as a nutritional supplement, and it can also improve feed performance. To assess the potential use of taurine as a feed attractant in plant protein-based diets, we examined four different concentrations of taurine to determine the optimal levels for attracting large yellow croaker (Larimichthys crocea). The fish displayed the most significant attractive responses to 3.5% taurine and showed good feed performance with an all-plant protein diet supplying 3.5% taurine. Next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
4
9
0
Order By: Relevance
“…We believe that fishes have limited olfactory-related receptors, which leads to limited olfactory ability, explaining why they do not exhibit significantly more intense behaviour with increased levels of odours. This suggests that fishes may possess a maximum detection peak for concentrations of certain stimuli, and a similar phenomenon has been observed in other studies ( Zhao, 2007 ; Hu et al, 2017 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We believe that fishes have limited olfactory-related receptors, which leads to limited olfactory ability, explaining why they do not exhibit significantly more intense behaviour with increased levels of odours. This suggests that fishes may possess a maximum detection peak for concentrations of certain stimuli, and a similar phenomenon has been observed in other studies ( Zhao, 2007 ; Hu et al, 2017 ).…”
Section: Discussionsupporting
confidence: 87%
“…To date, three types of receptor genes have been identified in fishes, namely olfactory receptors (ORs) ( Freitag et al, 1998 ), vomeronasal receptors (VRs) ( Freitag et al, 1995 ), and trace amine-associated receptors (TAARs) ( Eisthen, 2004 ). Among them, OR genes play an essential role in many odor detecting activities ( Hu et al, 2017 ; Yabuki et al., 2016 ; Bird et al., 2018 ). ORs encoding G protein-coupled receptors expressed in ciliated sensory neurons were previously identified in Rattus norvegicus ( Buck & Axel, 1991 ).…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids can bind to olfactory-related receptors that activate the G protein to transfer the olfactory signal (Saberi and Seyed-allaei, 2016, Ronnett and Moon, 2002). In the present study, OR, VR, and TAAR, three olfactory receptor gene families in sh, were all observed to be differentially expressed, which was consistent with our previous study (Hu et al, 2017). We suggested that a single amino acid could stimulate the three receptors which may work synergistically for the production of olfactory signal.…”
Section: Olfactory-related Receptors For Amino Acids In Silver Pomfretsupporting
confidence: 92%
“…Amino acids are common components of the natural prey of shes, and even in the presence of single amino acid, olfactory receptors of shes can bind it and trigger feeding behaviors (Hara, 2010, Franklyn et al, 2017. Therefore, amino acids are considered good phagostimulants when mixed with feed (Hu et al, 2017, Bell et al, 1996, and these phagostimulants can signi cantly affect the appetite of sh through their olfactory neural circuitry (Tandler et al, 1982, Koide et al, 2009. Odorant molecules released into the environment bind to olfactory-related receptors (Kaupp, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al . () analyzed the olfactory epithelial transcriptomics in large yellow croaker to identify the gene expression pattern regulated by taurine.…”
Section: Current Status Of Transcriptomics In Aquaculturementioning
confidence: 99%